No causal association between pneumoconiosis and three inflammatory immune diseases: a Mendelian randomization study - Yu-Jie Du; Yu-Jie Du; Zhang-Wei Lu; Zhang-Wei Lu; Kai-Di Li; Kai-Di Li; Yi-Yu Wang; Yi-Yu Wang; Hong Wu; Hong Wu; Rong-Gui Huang; Rong-Gui Huang; et al. (Frontiers Media S.A., 2024)
ObjectivesTo investigate the causal relationships between pneumoconiosis and rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and gout.MethodsThe random-effects inverse variance weighted (IVW) approach was utilized to explore the causal effects of the instrumental variables (IVs). Sensitivity analyses using the MR-Egger and weighted median (WM) methods were did to investigate horizontal pleiotropy. A leave-one-out analysis was used to avoid the bias resulting from single-nucleotide polymorphisms (SNPs).ResultsThere was no causal association between pneumoconiosis and SLE, RA or gout in the European population [OR = 1.01, 95% CI: 0.94-1.10, p = 0.74; OR = 1.00, 95% CI: 0.999-1.000, p = 0.50; OR = 1.00, 95% CI: 1.000-1.001, p = 0.55]. Causal relationships were also not found in pneumoconiosis due to asbestos and other mineral fibers and SLE, RA and gout [OR = 1.01, 95% CI: 0.96-1.07, p = 0.66; OR = 1.00, 95% CI: 1.00-1.00, p = 0.68; OR = 1.00, 95% CI: 1.00-1.00, p = 0.20].ConclusionOur study suggests that pneumoconiosis may have no causal relationship with the three inflammatory immune diseases.